A atuação das principais empresas do setor de telecomunicações no Cone Sul e digitalização do território - Paulo Fernando Jurado da Silva (Confins)
Our century witnesses the expansion of the digitization of the territory, with the adoption and use of information and communication technologies. The penetration of this phenomenon has recently been reinforced due to the COVID-19 pandemic and its ensuing consequences, including social isolation, the growth of remote work, and economic activities related to the use and dissemination of the Internet. Given this observation, the main objective of this work is to analyze the performance and corporate strategies of the largest telecommunications companies in the Southern Cone, which comprises nations in South America with diverse territorial and economic characteristics (Brazil, Argentina, Paraguay, Uruguay, and Chile), in the context of the digitization of the territory, particularly the expansion of telecommunications services and participation in national markets. For this study, several approaches were employed, including literature review on the subject, the search for secondary data on electronic websites, document and content analysis, data tabulation, and corresponding cartographic production. The study aims to provide interpretive elements to understand this reality, significant to geography and its neighboring fields, through the description of the characteristics of the underlying process and the highlighting of the specific ways in which commercial companies use the territory.